Study the spray characteristic and mixture of diesel-water compare with biodiesel on fractal grid turbulence generated using schlieren method in burner system - Amirnordin, Shahrin Hisham; Sahari, M.F.; Khalid, Amir; Ahmad Shaffie, Muhammad Elyas Muiz; Muhammad Usman, Abdullahi (FAZ Publishing, 2020)
In the global world nowadays, diesel is widely use with the high demand for fuel in automotive and burner system. Diesel fuel release harmful gases to the surrounding when it been use. Therefore, various study has been done for controlling the levels of harmful gas emission and air pollutants. Fractal grid is the component located in rapid mixing injector that can improve the formation of a mixture on fuel and air in the combustion process. Fractal grid also can increase the length of penetration achieve high combustion velocity in the combustion process and reduce emission. The objective of this study was to determine the effect of fractal grid towards spray characteristic and mixture of fuel and air in burner system. Schlieren method will be used to capture image of spray which the spray characteristic such as spray tip penetration, spray angle and spray area to be analyzed. Spray image will be compared with different groups of images that have been taken. The air to fuel ratio is good combination to the fractal grid which it can provide good spray behavior and reduce emission. This experiment will be used three types of fractal grid with different geometry. The experiment also uses diesel and biodiesel (B5, B10, B15) with addition of water content (W0, W5, W10, W15). This study found that the increase in the equivalent ratio made the long spray penetration and wide spray while the spray angle is smaller. Lastly, fractal grid is turbulence generator for the mixture of diesel-air for reduce emission.